THE USE OF PHONICS INSTRUCTION TO ENHANCE STUDENTS’ READING ABILITY: A CASE STUDY OF GRADE 3 STUDENTS AT NAM YUEN SCHOOL, NAM YUEN DISTRICT, UBON RATCHATHANI PROVINCE - Thaen-nga, Jidanan; Leenam, Wutti (International Journal of Research -GRANTHAALAYAH, 2016)
The purpose of this research was to study English reading ability after being taught through the phonics instruction. The target group was 30 Grade 3 students enrolled in English course in the second semester of academic year 2015 at Nam Yuen School, Nam Yuen District, UbonRatchathani Province. The experimental instrument was 5 lesson plans using phonics instruction. The instruments were the tests used before starting and after finishing each lesson. The data obtained were analyzed using mean, percentage and standard deviation. The findings revealed a statistically significant main effect (P <.001) indicating that there was a significant difference between the mean scores of the pretest and the posttest which means that the students increased their oral reading ability after being taught through phonics.